Liraglutide for the Treatment of Obesity: Analyzing Published Reviews - Pastor, Rosario; Tur, Josep A. (Current Pharmaceutical Design, 2019)
Background: Several drugs have been currently approved for the treatment of obesity. The pharmacokinetic of liraglutide, as well as the treatment of type 2 diabetes mellitus, have been widely described. Objective: To analyze the published systematic reviews on the use of liraglutide for the treatment of obesity. Methods: Systematic reviews were found out through MEDLINE searches, through EBSCO host and the Cochrane Library based on the following terms:
Keywords: glucagon-like peptide-1 receptor agonist (GLP-1)